2022
DOI: 10.1007/978-3-030-79353-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Impact of Human Resources on the Efficiency of Healthcare Systems and Person-Centred Care

Abstract: We explore the alternative explanation for barriers and facilitators for implementation of PCC evolving from human resources through the lenses of institutional theory. We have deepened the explanation by adding the perspective of different institutional logics, which shows that the physician's resistance or nurses’ support may originate from the differences in institutional logics. Working with patients by applying person-centered principles places new demands on health professionals. It is widely agreed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Goncharuk (2018) and Goncharuk et al (2020) found significant differences in the motivation of health workers in different countries. Medical staff in efficient and inefficient healthcare systems has different influencing motivators (Knezevic et al, 2022). Peters et al (2010) noted a difference in the motivation of health workers in the public and private healthcare sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Goncharuk (2018) and Goncharuk et al (2020) found significant differences in the motivation of health workers in different countries. Medical staff in efficient and inefficient healthcare systems has different influencing motivators (Knezevic et al, 2022). Peters et al (2010) noted a difference in the motivation of health workers in the public and private healthcare sectors.…”
Section: Literature Reviewmentioning
confidence: 99%